Synthesis, crystal structure, spectral properties and catalytic activity of a binuclear copper(II) complex containing a Schiff base ligand - Pattanayak, Poulami
The newly designed multidentate ligand HL, derived from 2-(benzylthio)aniline and 2-hydroxy-5-methylbenzene-1,3-dialdehyde, upon reaction with Cu(II) perchlorate in methanol yielded the binuclear Cu(II) complex [Cu-2(L)(mu-OH)](ClO4)(2) (1), which was authenticated by single crystal X-ray diffraction. The diffraction analysis revealed that the ligand binds each of the two Cu(II) centers in an (O, N, S) fashion in a distorted square pyramidal geometry where the two copper centers are bridged by mu-phenoxo and mu-hydroxo oxygen atoms. The apical position of one copper center is coordinated by one perchlorate ion and the other center by a water molecule. The packing of the molecule is stabilized through OH2 center dot center dot center dot O hydrogen bonds, mediated through solvent water and perchlorate anions. The emission and redox properties of both the ligand and the complex were examined. The electronic spectra and redox properties of the complex have been explained with DFT computations. The complex [Cu-2(L)(mu-OH)](ClO4)(2) shows very good catalytic activities towards the oxidation of benzyl alcohol to benzaldehyde and organic thioethers to the corresponding sulfoxide and sulfones using H2O2 as the oxidant. (C) 2013 Elsevier Ltd. All rights reserved.